2008
DOI: 10.1152/ajpgi.90443.2008
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen prevents intestinal inflammation after trauma-hemorrhage via downregulation of angiotensin II and angiotensin II subtype I receptor

Abstract: Although angiotensin II (Ang II) plays a key role in development of organ ischemia-reperfusion injury, it remains unclear whether it is involved in development of intestinal injury following trauma-hemorrhage (T-H). Studies have shown that 17β-estradiol (E2) administration following T-H improves small intestinal blood flow; however, it is unclear whether Ang II plays a role in this E2-mediated salutary effect. Male Sprague-Dawley rats underwent laparotomy and hemorrhagic shock (removal of 60% total blood volum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 51 publications
(49 reference statements)
0
9
0
1
Order By: Relevance
“…It is known that the GI RAS plays important roles in a variety of intestinal processes, including absorption and secretion, motility and inflammation [ 27 , 28 , 30 ]. The local GI RAS has also been related to GI diseases such as inflammatory disorders [ 34 , 35 ], GI motility disorders, mesenteric ischemia and GI cancer [ 27 - 30 ]. The present results are also consistent with a number of studies in different tissues showing that overactivation of local or tissue RAS, via AT1 receptors and NADPH oxidase activation, mediates oxidative stress and several key events in inflammatory processes that play a major role in several aging-related diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the GI RAS plays important roles in a variety of intestinal processes, including absorption and secretion, motility and inflammation [ 27 , 28 , 30 ]. The local GI RAS has also been related to GI diseases such as inflammatory disorders [ 34 , 35 ], GI motility disorders, mesenteric ischemia and GI cancer [ 27 - 30 ]. The present results are also consistent with a number of studies in different tissues showing that overactivation of local or tissue RAS, via AT1 receptors and NADPH oxidase activation, mediates oxidative stress and several key events in inflammatory processes that play a major role in several aging-related diseases [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been shown that expression of vascular and renal AT1 receptors, as well as the balance between AT1 and AT2 receptors may be modulated by sex hormones, and a major role for RAS in the gender differences in the development of chronic renal and cardiovascular diseases has been proposed [ 10 - 12 ]. Several studies have revealed that estrogen-mediated down-regulation of the renin-angiotensin system (RAS) mediates beneficial effects of estrogen (E2) in several tissues [ 16 - 18 ]. Furthermore, there is substantial evidence that androgens may upregulate RAS activity and therefore amplify gender-related differences [ 10 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, some reported effects of estrogen replacement therapy are controversial (Shulman, 2002 ; Popat et al, 2005 ), and the age and duration of lack of estrogen in women receiving the treatment appear to be major factors in the discrepancies. Interestingly, estrogen-induced regulation of the RAS mediates beneficial effects of estrogen in several tissues (Nickenig et al, 1998 ; Dean et al, 2005 ; Chen et al, 2008 ), and interactions between estrogen and AII receptors have also been observed (Liu et al, 2002 ; Tsuda et al, 2005 ; Xue et al, 2007 ; Hoshi-Fukushima et al, 2008 ). In several recent studies we have observed that the lack of estrogen increases RAS activity in the substantia nigra in females (Rodriguez-Perez et al, 2010 , 2011 , 2012 ).…”
Section: Dopaminergic Vulnerability In Aging Menopause and Brain Hypmentioning
confidence: 99%